Optimized calculation of the synergy conditions between electron cyclotron current drive and lower hybrid current drive on EAST *Project supported by the National Magnetic Confinement Fusion Science Program of China (Grant Nos. 2011GB102000, 2012GB103000, and 2013GB106001), the National Natural Science Foundation of China (Grant Nos. 11175206 and 11305211), the JSPS-NRF-NSFC A3 Foresight Program in the Field of Plasma Physics (Grant No. 11261140328), and the Fundamental Research Funds for the Central Universities of China (Grant No. JZ2015HGBZ0472). (8th December 2015) - Wei 韦, Wei 维; Ding 丁, Bo-Jiang 伯江; Peysson, Y; Decker, J; Li 李, Miao-Hui 妙辉; Zhang 张, Xin-Jun 新军; Wang 王, Xiao-Jie 晓洁; Zhang 张, Lei 磊
Abstract: The optimized synergy conditions between electron cyclotron current drive (ECCD) and lower hybrid current drive (LHCD) with normal parameters of the EAST tokamak are studied by using the C3PO/LUKE code based on the understanding of the synergy mechanisms so as to obtain a higher synergistic current and provide theoretical reference for the synergistic effect in the EAST experiment. The dependences of the synergistic effect on the parameters of two waves (lower hybrid wave (LHW) and electron cyclotron wave (ECW)), including the radial position of the power deposition, the power value of the LH and EC waves, and the parallel refractive indices of the LHW ( N ∥ ) are presented and discussed.